The Difference of Anxiety Level on Hemodyalisis Patient Applied Health Education Using Leaflet and Audiovisual Aids - Nurhidajah -; Shobirun -; Arwani - (Universitas Muhammadiyah Semarang, 2011)
Background - End stage renal disesase (ESRD) or chronic kidney disease is a life treatening condition. One of treatment conducted to replace renal function is hemodyalis. Among several patients, hemodyalisis can be a stressor for the patients so that anxiety is a condition that often experienced by the patients. In several cases, anxiety causes the patient fall in deteriorating condition at the time hemodyalisis done. Researches show that the quality of life of renal failure patients depend on the ability to face a steessor. In General Hospital Kota Semarang, health promotion has been developed. However, the implementation has not been conducted through audiovisual or leaflet media so that it may be contributed to low level knowledge. As a result, anxiety may increase. Objective - This study aimed to analise the difference of enxiety level of patient who having health education through audiovisual and leaflet media in Renal Unit General Hospital Kota Semarang. Method - Thirty nine respondent were partisipated in this study. Pre-test post-test design was applied to identify anxiety level of the patients. Independent t Test was used to analised the differences between two groups. Result - The result showed that there was significant difference when the patients having audiovisual (p=0.007) and when having leaflet (p=0.000). Meanwhile, there was no significant difference between both use of leaflet and audiovisual media (p=0.713). Recommendation - This study recommended the importance of using both leaflet and also audiovisual media. Key words - End Stage Renal Disesase (ESRD), I-Iemodyalisis Anxiety, Leaflet Audiovisual Medi